Transit infrastructure finance through station location auctions - Ian Carlton (University of California, Institute of Urban and Regional Development (IURD), 2009)
With increased interest in new transit systems for congestion relief, or pollution mitigation and limitations on the amount of funding available, governments and planners are looking at many new ways to finance transit infrastructure. One method being pursued is capturing some of the value conferred to sites when transit is introduced. This paper discusses a proposal to capture that value through a market based bid process, examines means of overcoming several related stakeholder issues, and discusses potential pilot project sites. As early as 1826, German economist Johann Heinrich von Thünen developed a theory that transport adds a measure of accessibility and value to a site. Research has continued for almost two centuries and UC Berkeley professor Robert Cervero has conducted several studies that identified a ten percent premium for locations that have enhanced accessibility due to transit's proximity. Capturing this value, though rare, is typically achieved through standard local finance mechanisms like property tax levies, assessment districts, and TIF. These methods have seen limited implementation as each presents significant issues for policymakers, transit operators, and the public, when compared to alternative grant funds from state or federal transport departments. In hopes of finding a new value capture alternative, this paper explores the possibility of a market-based bid system where property owners volunteer a portion of the anticipated increase in value to deliver the property enhancing transit infrastructure. These "bids" would help determine the optimal location for transit based on a cost/benefit analysis of various route and station alignments. This concept was originally developed in the author's graduate thesis research at the Department of City and Regional Planning. Subsequent coursework outlined the process, identified stakeholders, and proposed techniques to mitigate potential stakeholder concerns. Important conclusions include identifying a need for a non-profit oversight entity to coordinate implementation and a focus on proposed transit systems that do not qualify for federal funding grants.
Keywords: 330